PROSES PEMBENTUKAN KONSEP DALAM MENEMUKAN KEMBALI TEOREMA PYTHAGORAS DAN MISKONSEPSI YANG TERJADI DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) - Mulyatna, Fauzi (ARITHMETIC: Academic Journal of Math, 2019)
This research aims to find out the process of concept formation in reinventing Pythagorean Theorem and to analyze the result of that process and the misconceptions that may emerge. The type of this research is qualitative research which is analyzed descriptively. This research applies class setting method in learning activity with the implementation of PMRI approach and it focuses on two subjects. The results shows that the process of concept formation in reinventing the Pythagorean Theorem with PMRI approach can work well. However, the two subjects have not been able to construct the given problem, which is in the form of a question, to be the form of a mathematical modeling. Subject 1 still processes the information rawly. Therefore, the result of concept finding with his/her knowledge used for solving problems by the same model has not been able to reduce data. Subject 2 has been able to process the obtained information and he/she can interpret the problem further. However, both subjects still experience misconceptions not only in their already possessed knowledge but also their newly acquired knowledge. Those misconceptions are misconception in calculating operation of equation system, which should be calculating operation on both segments but it is only carried out in one segment, misconception in describing hypotenuse and misconception in naming edges of a right triangle.